The importance of hematologic indices in the risk stratification of patients with acute decompensated systolic heart failure - Nihat Polat; Abdulkadir Yildiz; Mehmet Zihni Bilik; Mesut Aydın; Halit Acet; Hasan Kaya; Muhammet Demir; Mehmet Ali Isik; Sait Alan; Nizamettin Toprak (KARE Publishing, 2015)
Objectives: In patients with heart failure, a variety of hemogram parameters are known to be of prognostic significance. This study aimed to investigate which of these parameters is/ are useful in predicting one-year all-cause mortality in patients with acute decompensated heart failure (ADHF). Study design: Patients who were hospitalized between September 2012-March 2013 in our hospital with systolic-ADHF with ejection fraction ≤40%, symptoms, and findings of congestion were enrolled retrospectively in the study. The study population was divided into two groups based on one-year-mortality. Results: 119 patients with ADHF (mean-age 67+-14 years; 55% male) were enrolled in the study. One-year-mortality occurred in 29% of patients. Hemoglobin levels, platelet, basophil and lymphocyte counts were significantly lower, while red-cell distribution width (RDW) was found to be significantly higher in the one-year-mortality group. Neutrophil, monocyte, and eosinophil counts were similar in the two groups. Furthermore, lower estimated glomerular-filtration-rate (eGFR) and unused angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARB) were associated with mortality. Age, presence of hypertension, right-ventricular diameter, eGFR, ACE/ARB treatment, hemoglobin levels, RDW and platelet, leukocyte, lymphocyte, basophil, neutrophil, monocyte, and eosinophil-counts were found to have prognostic significance in univariate analysis. In multivariate analysis, decreased platelet, lymphocyte-counts and hemoglobin level on admission and unused ACE/ARB treatment at discharge (p<0.05) were found to be independent factors predicting one-year-mortality. Conclusion: Among hematological indices; hemoglobin level, platelet and lymphocyte counts are readily available, useful and inexpensive markers for the prediction of one-year allcause mortality in ADHF patients.